A retrospective study evaluating the tolerability and effectiveness of adjunctive antihypertensive drugs in patients with inadequate response to initial treatment. Issue 6 (13th June 2018) - Ayyagari, Rajeev; Xie, Jipan; Cheng, David; Wu, Eric Q.; Huang, Xing‐Yue; Chen, Stephanie
Abstract : Real‐world tolerability and effectiveness of nebivolol as first add‐on therapy were compared with hydrochlorothiazide, metoprolol, and amlodipine. Medical records of hypertensive adults initiating nebivolol, hydrochlorothiazide, metoprolol, or amlodipine as first add‐on therapy between December 16, 2010 and July 21, 2011 were retrospectively abstracted (N = 1600; 400/treatment). Outcomes included medication‐related side‐effect rates and blood pressure (BP) reduction and control. Compared with nebivolol, metoprolol and amlodipine had significantly higher side‐effect rates (incidence rate ratio [95% CI]: 1.82 [1.14‐2.92] and 2.67 [1.69‐4.21]), respectively); the hydrochlorothiazide‐nebivolol rate ratio was not significant (1.61 [0.95‐2.71]). All treatments reduced BP at 2 months. Metoprolol, amlodipine, and hydrochlorothiazide were associated with significantly lower odds of achieving 2‐month BP control than nebivolol (odds ratios [95% CI]: 0.34 [0.23‐0.51], 0.51 [0.35‐0.75] and 0.66 [0.44‐0.99], respectively). In a real‐world setting, nebivolol as first add‐on therapy was associated with fewer side effects than metoprolol or amlodipine and with a higher BP control rate than hydrochlorothiazide, metoprolol, or amlodipine.